Effects of L-carnitine supplementation on physical performance and energy metabolism of endurance-trained athletes: a double-blind crossover field study - Colombani, P.; Wenk, C.; Kunz, I.; Krahenbuehl, S.; Kuhnt, M.; Arnold, M.; Frey-Rindova, P.; Frey, W.; Langhans, W. (European Journal of Applied Physiology, 1996)
A double-blind crossover field study was performed to investigate the effects of acute L-carnitine supplementation on metabolism and performance of endurance-trained athletes during and after a marathon run. Seven male subjects were given supplements of 2 g L-carnitine 2 h before the start of a marathon run and again after 20 km of the run. The plasma concentration of metabolites and hormones was analysed 1 h before, immediately after and 1 h after the run, as well as the next morning after the run. In addition, the respiratory exchange ratio (R) was determined before and at the end of the run, and a submaximal performance test was completed on a treadmill the morning after the run. The administration of L-carnitine was associated with a significant increase in the plasma concentration of all analysed carnitine fractions (i.e. free carnitine, short-chain acylcarnitine, long-chain acylcarnitine, total acid soluble carnitine, total carnitine) but caused no significant change in marathon running time, in R, in the plasma concentrations of carbohydrate metabolites (glucose, lactate, pyruvate), of fat metabolites (free fatty acids, glycerol, beta-hydroxybutyrate), of hormones (insulin, glucagon, cortisol), and of enzyme activities (creatine kinase, lactate dehydrogenase). Moreover, there was no difference in the result of the submaximal performance test the morning after the run. In conclusion, acute administration of L-carnitine did not affect the metabolism or improve the physical performance of the endurance-trained athletes during the run and did not alter their recovery.